Hyaluronic acid gel as a nonsurgical approach for the interdental papillary defects: A systematic review - Daniele Sorgatto Faé; Sibele Nascimento de Aquino; Fernanda Oliveira Bello Correa; Cleverton Corrêa Rabelo; Ana Emília Farias Pontes; Cleidiel Aparecido Araujo Lemos (Elsevier, 2023)
Objetive: This systematic review aimed to evaluate whether the use of HA could be considered an effective treatment approach for the restoration of papillary defects. Material and methods: This study was registered on the PROSPERO. A systematic search was performed on five electronic databases for articles published up to May 2022. The meta-analysis was performed using the R program. The risk of bias and quality was assessed using the RoB 2.0 and National Institutes of Health, respectively. Results: Eighteen studies were included with a total of 213 participants with 696 interdental papillary defects. All included studies reported promising results on the reconstruction of the deficient interdental papilla after injection of HA. Single-arm meta-analysis indicated a proportion of 47% (confidence interval [CI]:35-59%) of sites evaluated with complete interdental papilla reconstruction (100% of reconstruction). Partial interdental papilla reconstruction (range from: 2.1% to 96% reconstruction) was reported by 49% (CI:40-59%) of sites evaluated. Five studies evaluated patient-reported outcome measures. An increased satisfaction was observed after the injection of HA without significant pain after the evaluation periods. Randomized controlled trials (RCT) studies presented a low and unclear risk of bias, while uncontrolled studies were classified as having good quality. Conclusion: The short-term analysis indicated that the injection of HA for the treatment of papillary defects is considered a feasible treatment achieving esthetic satisfactory results with minimum pain. However, further well-conducted RCT studies with standardized parameters and long-term follow-up should be recommended.